Terfenadine, a histamine H1 receptor antagonist, induces apoptosis by suppressing STAT3 signaling in human colorectal cancer HCT116 cells - Baniya, Manoj Kumar; Kim, Eun-Hee; Chun, Kyung-Soo (Frontiers in Pharmacology, 2024)
Colorectal cancer is a highly aggressive and metastatic cancer with inadequate clinical outcomes. Given the crucial role of histamine and histamine receptors in colorectal carcinogenesis, this study aimed at exploring the anticancer effects of terfenadine against colorectal cancer HCT116 cells and elucidate its underlying mechanism.: Herein, we examined the effect of terfenadine on growth and proliferation of HCT116 cells in vitro and in vivo. Various experimental techniques such as flow cytometry, western blot, immunoprecipitation, luciferase assay were employed to unveil the mechanism of cell death triggered by terfenadine. Results: Terfenadine markedly attenuated the viability of HCT116 cells by abrogating histamine H1 receptor (H1R) signaling. In addition, terfenadine modulated the balance of Bax and Bcl-2, triggering cytochrome c discharge in the cytoplasm, thereby stimulating the caspase cascade and poly-(ADP-ribose) polymerase (PARP) degradation. Moreover, terfenadine suppressed murine double minute-2 (Mdm2) expression, whereas p53 expression increased.Terfenadine suppressed STAT3 phosphorylation and expression of its gene products by inhibiting MEK/ERK and JAK2 activation in HCT116 cells. Furthermore, treatment with U0126, a MEK inhibitor, and AG490, a JAK2 inhibitor, dramatically diminished the phosphorylations of ERK1/2 and JAK2, respectively, leading to STAT3 downregulation. Likewise, terfenadine diminished the complex formation of MEK1/2 kinase with β-arrestin 2.In addition, terfenadine dwindled the phosphorylation of PKC substrates. Terfenadine administration (10 mg/kg) substantially retarded the growth of HCT116 tumor xenografts in vivo.signaling. Overall, this study supports terfenadine as a prominent anticancer therapy for colorectal cancer.